Meningkatkan Kemampuan Motorik Anak Usia Dini Melalui Latihan Yoga Asanas - Putu Emy Suryanti; Kadek Bayu Indrayasa (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
One of the visions of national development to develop human resources is realized by providing education aimed at developing intelligence holistically which includes cognitive, social, emotional, aesthetic and kinesthetic, as well as affective and psychomotor abilities. There are two components of mobility that need to be developed in children, namely: basic movement skills/gross motor skills and fine motor skills. This motor skills are very vital for children to be able to be independent in their future lives, so the right stimulus is needed to be able to get optimal motor skills of children. One of the stimuli that can be given to children is by practicing yoga ?sana. Movements in yoga ?sana that are done in a disciplined and regular manner from an early age can improve motor skills of children. Keywords: motor skills, early childhood, yoga ?sana.